Lagoa modular multifuncional para tratamento de efluentes líquidos com base em processos biotecnológicos - Tonhato Junior, Alcides (2018)
In industrial wastewater treatment systems, the use of stabilization ponds prevails, but low performance results still persist, associated with the necessity of large surface areas occupied, difficulty in maintenance, inefficiency in operation, accumulation of rainwater, occurrence of preferential paths, dead zones formation, the absence of well defined geometric pattern, proliferation of unwanted organisms, ecological problems related to the local fauna, unpleasant odors, difficulty in monitoring, adjustment and controlling of operational parameters. Towards that scenario, the arguments of the thesis are: conventional lagoons, although widely used, do not constitute efficient technological options; industrial wastewater should not always be considered as a synonym to problems, when properly treated, they may present opportunities for exploitation, as a raw material for other transformation processes. In this context, the present work had as objective, the development and proposal of an innovative technology for the treatment of industrial liquid effluents based on biotechnological processes, in contrast to conventional lagoon systems. For this purpose, the methodology contemplated the accomplishment of 10 steps: 1) the characterization of the sources of industrial wastewater generation; 2) the qualitative and quantitative characterization of the wastewater of the industry under study; 3) exploration of methods, processes and technologies for the treatment of industrial wastewater; 4) the development of the alternative wastewater treatment system; 5) the planning, design, construction and assembly of the prototype (new technological solution); 6) the operationalization and experimental planning of the system; 7) the monitoring and operational controlling of variables and parameters; 8) analysis and systematization of results; 9) the evaluation of intellectual protection requirements; and 10) systematization and formatting of the new technological solution for the treatment of industrial wastewater (main object of work). The modular bioreactor developed in this work was constructed in reinforced concrete with 70 m length, 1.2 m wide and 0.6 m high, with an internal volume of 35000 L, the degradation process alternates between aerobic and anoxic conditions, being mostly anoxic. The main differentials of the equipment are found: in the continuous operation, in the multifunctional characteristic due to the auxiliary devices that provide the primary, secondary and tertiary treatment in the same equipment, in the practicality of the maintenance and also in the possibility of interrupting each module without compromising the operational continuity, in eliminating the formation of dead zones, short circuiting and deviations of untreated wastewater, in the serial or parallel operational arrangement, in the modular characteristic, which makes possible the implantation of auxiliary devices, in the ease of control and adjustment of operational parameters, in controlling the proliferation of undesired organisms, in the compact characteristic, when compared to conventional ponds, in the flexibility of the treatment capacity/flow rate of the wastewater, which is achieved by adding or subtracting modules according to demand, in the existence of the retractable roof, and module geometry that facilitates the deployment of auxiliary devices. The module was promising in the treatment of the effluents from slaughterhouses wastewater after primary treatment, and the best result showed removal of 76.09% COD, 96.67% BOD, 22.86% total Nitrogen, 27.50% of Ammonia, 62.5% of Nitrite, 7.9% of Nitrate, 81.30% of total Phosphorus, 86.18% of total solids and 98.54% of oils and greases, operating with feed rate of 605.17 L h-1 and residence time of 2.41 days. Partial nitrification may have occurred on a continuous scale in the first stage of the tests. The bioreactor used in this research was deposited at the National Institute of Intellectual Property, entitled "Multifunctional modular pond for treatment of wastewater based on biotechnological processes" (nº BR 20 2018 002560 6, deposited in 07/02/2018). Thus, the development of this environmental technology contributes to the sustainability of industrial activities.